2021
DOI: 10.3892/etm.2021.10190
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and therapeutic features of acute cholecystitis in diabetic patients

Abstract: The present study aimed to compare the clinical, paraclinical, intraoperative findings, and postoperative complications in acute cholecystitis in diabetic patients vs. non-diabetic patients. A 2-year retrospective study was performed on the patients who underwent emergency cholecystectomy for acute cholecystitis between 2017 and 2019 at the 4th Department of Surgery, Emergency University Hospital Bucharest. The diabetic subgroup numbered 46 eligible patients and the non-diabetic one 287 patients. Demographics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Consequently, the data that might have impacted this study, such as an underlying disease, were not collected. For example, patients with diabetes tended to have more severe clinical features than non-diabetic patients [ 24 ]. Besides, the previous article focusing on clinical features of acute cholecystitis found that >2 mg/mL of serum creatinine was observed in diabetic patients, which is more than in non-diabetes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the data that might have impacted this study, such as an underlying disease, were not collected. For example, patients with diabetes tended to have more severe clinical features than non-diabetic patients [ 24 ]. Besides, the previous article focusing on clinical features of acute cholecystitis found that >2 mg/mL of serum creatinine was observed in diabetic patients, which is more than in non-diabetes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with diabetes tended to have more severe clinical features than non-diabetic patients [ 24 ]. Besides, the previous article focusing on clinical features of acute cholecystitis found that >2 mg/mL of serum creatinine was observed in diabetic patients, which is more than in non-diabetes [ 24 ]. Furthermore, because several different levels of doctors are working in the ED, some physical examination requires both skill and experience in interpreting.…”
Section: Discussionmentioning
confidence: 99%
“…It is the treatment of choice for cholelithiasis with symptoms mostly biliary colic, acute cholecystitis, obstructive jaundice, or gallstone pancreatitis [9]. Other indications of cholecystectomy are complications of gallstone, that is acute calculus cholecystitis, gallstone in common bile duct, pancreatitis caused by gallstones, biliary dyskinesia, gall bladder polyps larger than 10 mm, cancer probability (calcified gallbladder) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies mention a higher degree of gallbladder distension and an increased wall tension secondary to kinetic disorders caused by microangiopathy and diabetic neuropathy. Metabolic disorders and DM-related gallstone formation may play a role that is not fully elucidated [21]. Chronically elevated blood sugar levels alter the immune response and render the diabetic more susceptible to infections by various mechanisms, such as glycosylation of the complement proteins, inhibition of immunoglobulin-mediated opsonization of bacteria, inhibition of neutrophil migration phagocytosis, and apoptosis [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, septic site infection and wound dehiscence were encountered to be more frequent in diabetic patients [25][26][27][28][29]. In this regard, the advantages of the laparoscopic approach are extremely important in preventing perioperative morbidity [21].…”
Section: Introductionmentioning
confidence: 99%